Tafsir on “Technological Apocalypse”: Reading Surah Al-Hajj [22] : 1-2 in the era of AI Singularity and Digital Disruption - Arip Dwi Iskandar; Ibnu Burdah; Nasihun Amin; Muhammad Mu'tamid Ihsanillah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study aims to (1) identify three dimensions of the digital crisis, ontological (AI singularity), relational (social disintegration), and epistemological (post-truth), through the lens of these verses; (2) construct a contextual exegesis relevant to the digital generation; and (3) formulate theological. and ethical implications for enhancing critical awareness within Muslim society. Employing a qualitative library research design with a thematic exegesis (maudhu’i) approach enriched by interdisciplinary analysis (digital psychology, philosophy of technology, media studies) and Braun & Clarke’s thematic analysis, this study offers contextual relevance: zalzalah (shaking) with the AI governance crisis, tadhyīl (a mother neglecting her child) with consciousness disruption and the attention economy, and sukārā (drunken without intoxication) with hyper-reality and digital addiction. The novelty of this study lies in the thematic reading linking three elements of the verse to three pillars of digital disruption, a multidisciplinary approach, and practical contributions to Qur’an-based digital literacy. The study further highlights implications including the reconstruction of epistemic authority (tabayyun), reaffirming human dignity, rebuilding social bonds, and prophetic critique of digital capitalism.